Crude glycerin levels in pearl millet-based diets for Nellore young bulls in feedlot - Moreira,Werney da Silva (2016)
ABSTRACT - The objective of this study was to find the best level of inclusion of crude glycerin (0, 60, 120, and 240 g kg−1 of dry matter of diet) in substitution of pearl millet in a feedlot diet. Twenty-eight Nellore young bulls with mean age of 18 months and average weight of 357±23.56 kg were used. The animals were distributed in a completely randomized design with four treatments and seven replications. The intakes of dry matter, crude protein, neutral detergent fiber, and total digestible nutrients were similar among the dietary levels of crude glycerin. The ether extract intake decreased with increase in the levels of crude glycerol in the diets. Apparent digestibility of dry matter, crude protein, and extract ether was similar among the dietary crude glycerin levels. Apparent digestibility of neutral detergent fiber was lower in the diets with inclusion of crude glycerin in relation the other diets. The increase in the levels of crude glycerin did not affect the total digestible nutrients content of the diets. Average daily gain increased linearly with the increase in crude glycerin. Feed conversion was not altered by the increase in the levels of crude glycerin in the diets. The dietary increase in crude glycerin level did not affect the carcass characteristics. The inclusion of up to 240 g kg−1 of crude glycerin in pearl millet grain-based diets for feedlot-finished Nellore young bulls increases average daily gain, but does not change the main carcass characteristics of economic importance.